Exploring the lived experience of mental health and coping during unemployment - Andrew F. Arena; Marnie Harris; Sophia Mobbs; Alexandra Nicolopoulos; Samuel B. Harvey; Mark Deady (BMC, 2022)
Abstract Background Unemployment is known to involve various psychosocial challenges that can negatively impact mental health. However, the intricacies of how individuals experience these challenges and strive to cope within the context of varied sociocultural and individuating factors, remain comparatively understudied. The present qualitative study used an interpretative phenomenological approach to explore the lived experiences of mental health and coping during unemployment. Methods Fifteen Australian adults who had recently experienced unemployment (for ≥3 months in the last 2 years), despite being available for and able to work, participated in semi-structured interviews from August to September 2021. Maximum variation sampling ensured participants represented diverse sociodemographic backgrounds. Interviews were audio-recorded, transcribed verbatim and analysed using reflexive thematic analysis within NVivo12 software. Results Four major themes were identified: 1) disrupted identity and direction in life; 2) navigating conflicting views of contribution and progress; 3) knowing how to cope is not enough; and 4) unemployment as a catalyst for new understandings. Unemployment disrupted participants' sense of purpose, identity and visions for the future. It signified a perceived failure to meet societal standards of value based upon the economic functions of work, which participants struggled to reconcile with their own priorities for work that satisfied psychosocial needs. Participants were aware of effective coping strategies, although these had mixed positive and negative effects on mental health, or were difficult to mobilise during unemployment. The COVID-19 pandemic, while normalising unemployment to some degree, exacerbated future uncertainty and prevented engagement with known coping strategies (e.g., social interaction). However, unemployment could also instigate growth through re-defining markers of achievement, re-aligning goals with one's core values, and developing greater compassion. Conclusions Experiences of mental health and coping during unemployment share complex relationships both with each other and with broader personal and sociocultural contexts. Service providers may better meet the mental health needs of those experiencing unemployment by balancing the economic and psychosocial functions of work, understanding that coping is a wholistic issue that goes beyond knowledge of effective strategies, and being aware of the opportunities for self-development that unemployment can create.